Evaluation of Ankle Fractures in 228 Patients From a Single Center Using Three-Dimensional Computed Tomography Mapping - Zeng, Jianshuang; Xu, Cheng; Xu, Gaoxiang; Zhang, Wupeng; Wang, Daofeng; Li, Hua; Gan, Xuewen; Xiong, Ying; Li, Jiantao; Zhang, Licheng; Tang, Peifu (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: The ankle joint has a complex anatomy structure with many causative factors and various injury mechanisms, and the clinical presentation of ankle fractures is diverse. This study aimed to analyze the characteristics of ankle fractures by applicating three-dimensional fracture line mapping technique. Methods: A retrospective study was conducted on 228 patients with ankle fractures. Three-dimensional reconstruction was performed by CT images and the fracture reconstruction model was superimposed onto a standard model of the tibiofibula for fracture line drawing. Then the fracture lines were converted into a three-dimensional coordinate point data set. And the fracture line maps as well as the fracture line heat maps were generated in 3-Matic software and Unigraphics NX software respectively. Results: The dense area of the fibular fracture lines was located above the tibiofibular joint ligament and wrapped obliquely around the distal fibula from the anterior edge of the fibular neck. The fibular fracture line could be divided into three categories according to the degree of denseness. The dense area of the tibial fracture line is located within the anterior tibial fornix, the anterolateral corner, and the fibular notch. The tibial fracture lines can be classified into four categories according to the density of the fracture lines. The combined medial malleolus + posterior malleolar fracture line situation was found to be not encompassed by the existing AO and Lauge-Hansen (LH) classification systems according to this classification. Conclusions: The 3D fracture line mapping technique can better reflect the distribution of ankle fracture lines and could help to establish a new ankle fracture typing system in the future.